2009
DOI: 10.1007/s11738-009-0323-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitric oxide in protection of tomato seedling against oxidative stress induced by osmotic stress

Abstract: Osmotic stress associated with drought and salinity is a serious problem that inhibits the growth of plants mainly due to disturbance of the balance between production of ROS and antioxidant defense and causes oxidative stress. In this research, sodium nitroprusside (SNP) was used as NO donor in control and droughtstressed plants, and the role of NO in reduction of oxidative damages were investigated. In this study, we observed that SNP pretreatment prevented drought-induced decrease in RWC and membrane stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
4
14
0
1
Order By: Relevance
“…In the present study, application of arginine, significantly increased the SOD activity, and suggested that application of this compound could promote the conversion of O × 2 into H 2 O 2 and O 2 , which is an important step in protecting the cell. The same result observed in SNP treated plants under drought stress (Nasibi and Kalantari 2009). If the produced H 2 O 2 cannot be scavenged efficiently, it can interact with O × 2 to form highly reactive hydroxyl radicals that are thought to be primarily responsible for oxygen toxicity in the cell.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the present study, application of arginine, significantly increased the SOD activity, and suggested that application of this compound could promote the conversion of O × 2 into H 2 O 2 and O 2 , which is an important step in protecting the cell. The same result observed in SNP treated plants under drought stress (Nasibi and Kalantari 2009). If the produced H 2 O 2 cannot be scavenged efficiently, it can interact with O × 2 to form highly reactive hydroxyl radicals that are thought to be primarily responsible for oxygen toxicity in the cell.…”
Section: Discussionsupporting
confidence: 69%
“…In previous research, we applied Sodium nitroprosside (SNP), an NO donor to counteract the effect of drought stresses on tomato plants (Nasibi and Kalantari 2009). However not any data are available on the effect of exogenous arginine as a precursor of NO in the possible antioxidative responses of plants against water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Ni excess in the environment also decreases chlorophyll content and growth in metal sensitive plants (Boominathan and Doran, 2002). Many abiotic environmental stresses including salinity, drought stress, temperature extremes, and metal toxicity disrupt the redox homeostasis of cells and exert a wide range of adverse effects on plant growth and metabolism (Sharma and Dubey, 2007;Nasibi and Kalantari, 2009). These stressful conditions induce overproduction of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…NO has also been involved in responses to abiotic and biotic stresses. It has been reported to exert a protective effect in response to drought stress (Lei et al 2007;Zhao et al 2008;Nasibi and Kalantari 2009), heat stress (Song et al 2006), heavy metal stress (Kopyra et al 2006;Singh et al 2008) and UV radiation stress (Shi et al 2005). The involvement of NO in salinity tolerance has drawn much attention in the past few years (Molassiotis et al 2010).…”
Section: Introductionmentioning
confidence: 99%